Triggering compatibility and dispersion by selective plasma functionalized carbon nanotubes to fabricate tough and enhanced Nylon 12 composites. (10th February 2015) - Roy, Sunanda; Das, Tanya; Zhang, Liying; Li, Yongmei; Ming, Yin; Ting, Sun; Hu, Xiao; Yue, Chee Yoon
Abstract: Here, we described a simple approach for the development of advanced composites based on Nylon 12 by selectively modified multiwalled carbon nanotubes (MWCNTs). Prior mixing, MWCNTs were modified by a new combination of plasma treatment i.e. oxygen + nitrogen (PL-MWCNTs) in order to improve its dispersion in the nylon matrix and enhance the interfacial adhesion by increasing the compatibility. With incorporation of only 1.2 wt % PL-MWCNTs, the tensile strength, Young's modulus, elongation at break and storage modulus of Nylon 12 were dramatically improved by ∼66%, 64%, 69% and 39%, respectively. These results were found to be higher than individual plasma treated CNTs. Such large increments were due to the effects of excellent homogeneous dispersion of PL-MWCNTs in the Nylon matrix and strong interfacial adhesion within themselves, which is believed to be effects of both oxygenated and nitrogenated functional groups generated on the surface of CNTs during plasma treatment. Graphical abstract: Highlights: A new plasma treatment process has been demonstrated for MWCNTs surface modification. This plasma treatment endowed various oxygenated and nitrogenated functional groups along with many amides on MWCNTs. Having same surface chemistry, this modified MWCNTs showed excellent compatibility and interface interactions with Nylon 12. As a result, the nanocomposites exhibited high mechanical strength and toughness.